Біотехнологія індукування стійкості рослин пшениці (Triticum aestivum L.) проти біотичного стресу - Жук, І.В.; Дмитрієв, О.П. (Фактори експериментальної еволюції організмів, 2015)
Aims. The usage of biological elicitors for plant defense responses against plant pathogenic fungi may initiate tolerance of plants and prevent environmental pollution. The aim of research was to investigate the effect of combined action of oxalic acid and NO in elicitation of wheat systemic resistance against Puccinia recondita f. sp. tritici agent during ontogenesis. Methods. The content of endogenous hydrogen peroxide was measured in leaves of winter wheat plants varieties Poliska 90 and Stolychna upon treatment of oxalic acid and leaf rust infection during ontogenesis. The morphometric parameters, degree of plant lesion and yield structure were analyzed. Results. Results obtained suggest that biotic elicitor – oxalic acid induces two wheat cultivars (Stolychna and Poliska 90) defense responses against leaf rust agent Puccinia recondita. Initiation of defense responses in elicitor-treated plants occurs in a short period of time. The effect of oxalic acid treatment increased the hydrogen peroxide content. The effect of oxalic acid also increased the grain quantity in ear and plant height. Conclusions. Biochemical nature of defense responses elicitation revealed an increase hydrogen peroxide content which induces lignin synthesis for mechanical strengthening of the cell wall. Keywords: hydrogen peroxide, oxalic acid, NO, Triticum aestivum L., Puccinia recondita f. sp. tritici leaf rust, plant defense responses.